Strategi Komunikasi Humas dalam Pengelolaan Dan Pelayanan Informasi di Kementerian Agama Kabupaten Dairi - Annisa Julianti Kudadiri (Universitas Katolik Widya Karya Malang, 2023)
This research aims to determine public relations communication strategies and supporting and inhibiting factors in information management and services at the Ministry of Religion, Dairi Regency. where the problem in this research began with the researcher being interested in analyzing the public relations communication strategies applied to the community in the form of policies, openness of public information and management of public opinion by the Ministry of Religion of Dairi Regency. This research uses qualitative research methods by collecting data through observation, documentation and interviews. The informant for this research is the Head of Public Relations of the Ministry of Religion, Dairi Regency, Mr. Haji Mahdi Kudadiri, S. Pdi, MM. Lindung Kaloko, S. Ag, Head of Bimas, Ministry of Religion, Dairi, Lespriono Munthe, S. Kom, Head of Public Relations, Ministry of Religion, Dairi, Saipul Bahri Capah, S. Pd, Public Relations Staff of the Ministry of Religion, Dairi, who researchers will interview and observe. The results of this research are: 1. Public relations communication strategy in information management and services by providing a forum for communication between the public and public relations in managing opinions through online, dialogue and letters. The reciprocal relationship that is built is in the form of responses given by the community where in social media there are many comment column features to convey opinions and suggestions to the Dairi Regency Ministry of Religion. 2. The supporting factor for the implementation of the strategy well is because each member collaborates with each other in carrying out news publications for the active existence of the Ministry of Religion's public relations in the management and information services in the Dairi Regency Ministry of Religion. There are no serious obstacles in implementing public relations strategies in providing information services needed by the public through various accesses, both online, letters and direct dialogue. The inhibiting factor in information management and services at the Ministry of Religion of Dairi Regency is the limited ability of officers in the field of technology.